Penerapan Kontrol Pencegahan Kontak Host-Vector dan Pembasmian Vector pada Model Penyebaran Penyakit Demam Berdarah - Dewi Erla Mahmudah; Atika Ratna Dewi (LPPM STMIK Widya Utama, 2018)
In this paper we discuss an existing denguedisease model with preventive control to minimize thecontact between host and vector. The model is furtherdeveloped involving the insecticide control to the vector.The aim is to obtain an optimal preventive strategies withminimal cost. We present the optimal control via thePontryagin Minimum Principle. The obtained optimalitysystem is derived by Hamiltonian function.